PELATIHAN PEMASARAN PRODUK DARI LIMBAH SEKAM PADI MENGGUNAKAN DIGITAL MARKETING DI DUSUN BEDENG - Duwi Rahma Putri; Annafi Indra Tama; Hadi Mahmudah (An-Nizam, 2022)
The main problem that occurs is the low quality of human resources in mastering technology and the lack of public understanding in terms of marketing. To overcome this problem, it is necessary to conduct marketing training using digital marketing. The purpose of implementing digital marketing training is to provide an understanding related to the importance of conventional and digital marketing. The implementation method used is through training which consists of the socialization stage about digital marketing, logos and labels, the training stage on how to operate the social media platform, and the evaluation stage of the activities that have been carried out. The results of the implementation of the community can distinguish between conventional marketing and digital marketing, understand how to create logos and labels on marketing and create WhatsApp Business and Instagram accounts as digital marketing. These two platforms were chosen because they are easy for the public to understand. However, the constraint of this training is the limited number of people who have smartphones.